PEMANFAATAN KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) SEBAGAI PENSTABIL ES KRIM SUSU KAMBING ETAWA UTILIZATION OF RED DRAGON FRUIT (Hylocereus polyrhizus) SKIN AS A STABILIZER FOR ETAWA GOAT’S MILK ICE CREAM - Risa Nisriinaa; Susilawati -; Fibra Nurainy; Suharyono - (Jurusan Teknologi Hasil Pertanian, 2024)
Red dragon fruit skin can be used as an additional ingredient in food. Red dragon fruit skin contains 10.80% pectin. The pectin content in the skin of red dragon fruit can be used as a stabilizer, one of which is an ice cream stabilizer. The aim of this research is to determine the effect of adding red dragon fruit peel flour as an ice cream stabilizer to produce ice cream with the best physical and sensory properties. The research was conducted using a Complete Randomized Block Design (RAKL) with a single factor consisting of 5 levels, namely the concentration of added red dragon fruit peel flour, namely 0.5%, 1%, 1.5%, 2%, and 2.5% and 4 repetition. As a control, 0.5% gelatin was used. The addition of red dragon fruit peel flour as an ice cream stabilizer has a significant effect on the taste, color, aroma, texture, overall acceptability, overrun, melting speed and stability of the ice cream emulsion. The addition of 1% red dragon fruit peel flour was the best treatment with a score for aroma of 2.79 (no prengus smell), texture of 3.15 (soft), color of 3.02 (liked), taste of 3.23 (liked) , overall acceptance of 3.27 (likes), overrun value of 69.69%, emulsion stability of 85.35 and melting speed of 53.83 minutes. Ice cream with the addition of dragon fruit peel flour contains 56.65% water content, 1.29% ash content, 6.32% fat, 4.96% protein and 30.78% carbohydrates.